When I'm calling you - Earl, Lawrence; Tietjen, Tina (London : Video Arts, 1978)
This video demonstrates how to deal with incoming calls, the training for all staff who takes outside calls. It concludes by showing how much easier it is to handle incoming calls correctly.
Keywords: Telephone etiquette